Uncertainties and uncertain risks of emerging biotechnology applications: A social learning workshop for stakeholder communication - Bouchaut, Britte; de Vriend, Huib; Asveld, Lotte (Frontiers in Bioengineering and Biotechnology, 2022)
Emerging applications of biotechnology such as new genomic techniques may give rise to new uncertainties and uncertain risks. Particularly the increased complexity and limited knowledge of possible risks associated with these new techniques, make it currently impossible to perform an adequate environmental risk assessment. As a result, there is a risk that such techniques don’t get beyond experiments demonstrating the proof of principle, stifling their further development and implementation. To break free from this deadlock, we must be able to learn what such uncertainties and uncertain risks entail, and how they should be assessed to ensure safe further development. To shape a responsible learning environment to explore uncertainties and uncertain risks, we have organized five stakeholder workshops. By means of a case about the genetic engineering of plants’ rhizosphere – an application abundant with uncertain risks – we identified tensions between different stakeholder groups and their different estimates of uncertainties and uncertain risks. Based upon derived insights, we developed a tool – a script for researchers to organize a stakeholder workshop – that enables a constructive discussion about emerging risks with a broad range of stakeholders. Thereby, the script provides a step-by-step approach to identify uncertainties, develop anticipatory strategies and adaptations in (experimental) research designs to lower or mitigate the earlier identified uncertainties, and helps to identify knowledge gaps for which (additional) risk research should be set up.